2014
DOI: 10.1063/1.4883915
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical spectroscopic investigations of HNSq and HSNq (q = 0, +1, −1) in the gas phase

Abstract: We performed accurate ab initio investigations of the geometric parameters and the vibrational structure of neutral HNS/HSN triatomics and their singly charged anions and cations. We used standard and explicitly correlated coupled cluster approaches in connection with large basis sets. At the highest levels of description, we show that results nicely approach those obtained at the complete basis set limit. Moreover, we generated the three-dimensional potential energy surfaces (3D PESs) for these molecular enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Ab initio calculations by Puzzarini (2005) indicated that it is bent with (B+C)/2 too low. HSN and HNS are both bent with singlet and triplet ground electronic states, respectively (Yaghlane et al 2014). Their cations are also bent with doublet ground electronic states and too low (B+C)/2 (Yaghlane et al 2014; Trabelsi et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio calculations by Puzzarini (2005) indicated that it is bent with (B+C)/2 too low. HSN and HNS are both bent with singlet and triplet ground electronic states, respectively (Yaghlane et al 2014). Their cations are also bent with doublet ground electronic states and too low (B+C)/2 (Yaghlane et al 2014; Trabelsi et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…HSN and HNS are both bent with singlet and triplet ground electronic states, respectively (Yaghlane et al 2014). Their cations are also bent with doublet ground electronic states and too low (B+C)/2 (Yaghlane et al 2014; Trabelsi et al 2016). Hence, no reasonable triatomic species can be found as carrier of our lines.…”
Section: Resultsmentioning
confidence: 99%
“…Similar analyses suggest that all the values of spectroscopic constants of the excited singlet states converge to a certain value respectively with the rise of basis set scale. Apparently, larger basis set would result in more accurate constants, as discussed in a series of carbenes and nitrenes . In the following sections, all the calculations were performed with the CBS basis set.…”
Section: Resultsmentioning
confidence: 99%
“…For the RCCSD(T) and CASSCF computations, we used the aug-cc-pV(X+d)Z (X = D, T, Q) basis sets for sulfur and the aug-cc-pVXZ (X = D, T, Q) for hydrogen and nitrogen atoms (Kendall and Dunning, 1992;Woon and Dunning, 1993;Dunning et al, 2001). The use of tight d functions for sulfur improves the quality of the results, as established in the benchmark computations presented in Refs ( BenYaghlane et al, 2013;Ben Yaghlane et al, 2014;Trabelsi et al, 2018), since it allows for a better description of the electron density of this polarizable atom and can provide accurate descriptions of the electronic structures of its compounds. In the RCCSD(T)-F12 calculations, the cc-pVXZ-F12 (X = D, T, Q) basis sets (Peterson et al, 2008) together with the corresponding auxiliary basis sets and density-fitting functions, as implemented in MOLPRO (Klopper, 2001;Weigend, 2002;Hättig, 2005), were used.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The list of identified species contains the NS, SH, NH, and NH 2 radicals as well as the H 2 S molecule. Other species are also very likely to be present there, such as HSN/HNS and their ions (Ben Yaghlane et al, 2014;Ajili et al, 2016;Trabelsi et al, 2016). In these media, these molecules and the H, N, and S atoms may undergo complex chemistry that may lead to the formation of larger molecular species, already detected or possibly present.…”
Section: Introductionmentioning
confidence: 99%